A comparison Analysis of Knowledge Management Process in International and Local Non-governmental Organizations Operating in Northeast Syria - Othman, Nechirvan A.; Istivan, Bartok I. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
This study examines the Knowledge Management (KM) processes within International Non-Governmental Organizations (INGOs) and Local Non-Governmental Organizations (LNGOs) operating in Northeast Syria (NES), We employ a survey methodology that comprises 34 items and measures four key KM processes: Building Knowledge, Holding Knowledge, Pooling Knowledge, and Using Knowledge. The survey was internet-based and distributed to both INGOs and LNGOs employees in NES Through a multi-stage approach utilizing volunteer and convenience sampling techniques, which achieved 101 responses. Descriptive and inferential analyses were conducted, including reliability tests, and mean comparisons, and the Mann-Whitney U test was used for hypothesis testing. Results indicate significant differences in Building and Using Knowledge between INGOs and LNGOs, with no significant differences in holding and pooling Knowledge. Which reflected in that INGOs exhibit a top-down approach to knowledge building, emphasizing learning from managers and experts. Conversely, LNGOs favor a more grassroots approach, highlighting innovation and improvement at the individual level. The study suggests that future research should explore the practical implications of KM processes within NGOs to enhance organizational performance and mission fulfillment. Specifically, an in-depth investigation into why LNGOs lag in holding knowledge compared to INGOs.